Justice Ontology; A Study of â€˜Umar Ibn Al-Khaá¹á¹Äbâ€™s IjtihÄd - Mansur, Ahsan Dawi; Murtiningsih, Siti (Al-Ahkam, 2021)
The paper was conducted to discover the nature of justice in the view of 'Umar Ibn Al-Khaá¹á¹Äb and to reveal his ijtihÄd from the point of view of a philosophical theory of justice. This research includes philosophical research that is historical-factual about a character with the type of library research then analyzes and presents it in a descriptive form. This paper finds that the essence of justice in the view of 'Umar Ibn Al-Khaá¹á¹Äb is acceptable behavior that is animated by the principle of equality. 'Umar Ibn Al-Khaá¹á¹Äb has applied the principle of equality before the law. He treats reason and revelation in harmony and balance in his ijtihÄd. 'Umar Ibn Al-Khaá¹á¹Äb drew inspiration from the intellect that Allah had given him by capturing universal values brought by the Koran, such as justice and equality, which are valid forever. This research contributes to the flexibility of 'Umar Ibn Al-Khaá¹á¹Äb in ijtihÄd, which is imbued with the principle of equality.